Fundamentals of CNS energy metabolism and alterations in lysosomal storage diseases. Issue 5 (12th November 2018) - McKenna, Mary C.; Schuck, Patricia F.; Ferreira, Gustavo C.
Abstract: The brain has a very high requirement for energy. Adult brain relies on glucose as an energy substrate, whereas developing brain can utilize alternative substrates as well as glucose for energy and for the biosynthesis of lipids and proteins required for brain development. Metabolism provides the energy required to support all cellular functions and brain development and building blocks for macromolecules. Lysosomes are organelles involved in breakdown of biological compounds including proteins and complex lipids in the body and brain. Recent studies suggest that lysosomal dysfunction can damage neurons and/or alter neurotransmitter homeostasis. Several studies also implicate mitochondrial dysfunction in the pathophysiology of brain damage in lysosomal storage diseases. This manuscript provides a brief review of energy metabolism and the key pathways involved in metabolism in brain. Roles of lysosomes related to metabolism and neurotransmission are discussed, and evidence for mitochondrial dysfunction in several lysosomal storage diseases is presented. This article is part of the Special Issue "Lysosomal Storage Disorders" . Abstract : Lysosomes are organelles involved in breakdown of biological compounds including proteins and complex lipids in the body and brain. Lysosomal dysfunction can damage neurons and other brain cells and/or alter neurotransmitter homeostasis. In this review, we discuss reciprocal interactions between malfunctioning mitochondria and lysosomes that may impact cell homeostasis and contribute to the pathophysiology of brain damage in lysosomal storage diseases. This article is part of the Special Issue "Lysosomal Storage Disorders" .